Ethnic Community Builders: Mexican-Americans in Search of Justice and Power - Jiménez, Francisco; García, Alma M.; Garcia, Richard A. (Rowman & Littlefield Publishers, 2007)
Ethnic Community Builders: Mexican-Americans in Search of Justice and Power is an oral history of Mexican-American activism in San JosZ, California, over the last half century. The authors present interviews of 14 people of various stripes—teachers, politicians, radio personalities—who have been influential in the development of a major urban center with a significant ethnic population. These activists tell the stories of their lives and work with engaging openness and honesty, allowing readers to witness their successes and failures. This vivid ethnography of a Mexican-American community serves as a model for activism wherever ethnic groups seek change and justice.